2013
DOI: 10.1186/1471-2474-14-24
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral and multiple cavitation sounds during upper cervical thrust manipulation

Abstract: BackgroundThe popping produced during high-velocity, low-amplitude (HVLA) thrust manipulation is a common sound; however to our knowledge, no study has previously investigated the location of cavitation sounds during manipulation of the upper cervical spine. The primary purpose was to determine which side of the spine cavitates during C1-2 rotatory HVLA thrust manipulation. Secondary aims were to calculate the average number of pops, the duration of upper cervical thrust manipulation, and the duration of a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
3
21
1
1
Order By: Relevance
“…We found the mean duration of a single pop to be 2.69 milliseconds during a lumbosacral HVLA thrust manipulation. This value is very similar to the 4-millisecond duration reported by Reggars and Pollard 28 for the "average length of joint crack sounds," the 5.66-millisecond duration for the mean duration of a single pop during upper cervical thrust manipulation, and 4.13 milliseconds during cervicothoracic junction thrust manipulation reported by Dunning et al 25,26 Although Herzog et al 3 reported triphasic "cavitation signals" with a mean duration of 20 milliseconds, it is unclear whether this value represents a single PS or multiple PSs. However, in our study, we calculated the time interval between the beginning of the ascent of the first energy burst and the end of the descent of the last energy burst of a PS event for the duration of a single pop.…”
Section: Duration Of An Individual Popsupporting
confidence: 87%
See 4 more Smart Citations
“…We found the mean duration of a single pop to be 2.69 milliseconds during a lumbosacral HVLA thrust manipulation. This value is very similar to the 4-millisecond duration reported by Reggars and Pollard 28 for the "average length of joint crack sounds," the 5.66-millisecond duration for the mean duration of a single pop during upper cervical thrust manipulation, and 4.13 milliseconds during cervicothoracic junction thrust manipulation reported by Dunning et al 25,26 Although Herzog et al 3 reported triphasic "cavitation signals" with a mean duration of 20 milliseconds, it is unclear whether this value represents a single PS or multiple PSs. However, in our study, we calculated the time interval between the beginning of the ascent of the first energy burst and the end of the descent of the last energy burst of a PS event for the duration of a single pop.…”
Section: Duration Of An Individual Popsupporting
confidence: 87%
“…The results of our study are difficult to compare directly with the previous studies 2, 17,25,28 on this topic. Similarly, Cramer et al 2 reported 93.5% of the PSs to have occurred on the upside facet articulations and with just 1.43 PSs per participant.…”
Section: Side Of the Pscontrasting
confidence: 87%
See 3 more Smart Citations